Habitat suitability for Swietenia macrophylla in climate change scenarios in Mexico - Ramírez-Magil, Gregorio; Botello, Francisco; Navarro-Martínez, María Angélica (Instituto de Ecología, A.C., 2020)
Ecological niche models allow determination of the habitat suitability of species. The objective of the present study was to determine habitat suitability for Swietenia macrophylla King (mahogany) under two scenarios of climate change in Mexico. For the modeling, the MaxEnt 3.3.3 algorithm was used. The species records of the 2009-2014 National Forest and the Soils Inventory were used as the primary source of information. The predictors were the raster of the observed and representative data interpolations for 19 bioclimatic variables, from 1960-1990, 2050 (average from 2041 to 2060), and 2070 (average from 2061-2080), RCP 4.5, the general circulation model MRI-Worldclim CGCM3 with a spatial resolution of approximately 1 km2, and the Comisión Nacional para el Conocimiento y Uso de la Biodiversidad edaphology raster with a spatial resolution of 90 m2. For the 2050 scenario, a loss of suitable habitat of 39.8% is projected, while for the 2070 scenario this loss is 47.6% compared to the 1960-1990 scenario. It is concluded that under both future scenarios, suitable habitat conditions will remain mainly in the states of Campeche and Quintana Roo, the latter of which will conserve about 50% of the suitable habitat. These results permit the development of strategies for the conservation, use and mitigation of the impact of climate change to ensure the survival and use of mahogany and the ecosystems in which it inhabits.